Metabolites of the Nitric Oxide (NO) Pathway Are Altered and Indicative of Reduced NO and Arginine Bioavailability in Patients with Cardiometabolic Diseases Complicated with Chronic Wounds of Lower Extremities: Targeted Metabolomics Approach (LC-MS/MS) - Krzystek-Korpacka, Małgorzata (Oxid Med Cell Longev, 2019)
OBJECTIVE: The status of metabolites of the nitric oxide (NO) pathway in patients with chronic wounds in the course of cardiometabolic diseases is largely unknown. Yet arginine supplementation and citrulline supplementation as novel therapeutic modalities aimed at increasing NO are tested. MATERIAL AND METHODS: Targeted metabolomics approach (LC-MS/MS) was applied to determine the concentrations of L-arginine, L-citrulline, asymmetric and symmetric dimethylarginines (ADMA and SDMA), and arginine/ADMA and arginine/SDMA ratios as surrogate markers of NO and arginine availability in ulnar and femoral veins, representing systemic and local levels of metabolites, in patients with chronic wounds in the course of cardiometabolic diseases (n = 59) as compared to patients without chronic wounds but with similar cardiometabolic burden (n = 55) and healthy individuals (n = 88). RESULTS: Patients with chronic wounds had significantly lower systemic L-citrulline and higher ADMA and SDMA concentrations and lower L-arginine/ADMA and L-arginine/SDMA as compared to healthy controls. The presence of chronic wounds in patients with cardiometabolic diseases was associated with decreased L-arginine but with increased L-citrulline, ADMA, and SDMA concentrations and decreased L-arginine/ADMA and L-arginine/SDMA. Serum obtained from the ulnar and femoral veins of patients with chronic wounds differed by L-arginine concentrations and L-arginine/SDMA ratio, both lower in the femoral vein. Wound etiology affected L-citrulline and SDMA concentrations, lower and higher, respectively, in patients with venous stasis, and the L-arginine/SDMA ratio—lower in venous stasis. The wound type affected L-arginine/ADMA and citrulline—lower in patients with ulcerations or gangrene. IL-6 was an independent predictor of L-arginine/ADMA, VEGF-A of ADMA, G-CSF of L-arginine/SDMA, and GM-CSF of L-citrulline and SDMA. CONCLUSION: Chronic wounds in the course of cardiometabolic diseases are associated with reduced NO and arginine availability due to ADMA and SDMA accumulation rather than arginine deficiency, not supporting its supplementation. Wound character seems to affect NO bioavailability and wound etiology—arginine bioavailability. Arginine concentration and its availability are more markedly reduced at the local level than the systemic level.